Factors Associated with Prescriptions for an Orexin Receptor Antagonist Among Japanese Patients with Insomnia: Analysis of a Nationwide Japanese Claims Database - Shoki Okuda; Zaina P. Qureshi; Yukiko Yanagida; Chie Ito; Yuji Homma; Shigeru Tokita (Adis, Springer Healthcare, 2023)
Abstract Background Few studies have examined the prescribing patterns of orexin receptor antagonists (ORAs) in the real-world clinical setting in Japan. Objective We sought to analyze the factors associated with ORA prescriptions for patients with insomnia in Japan. Methods Outpatients (aged ≥ 20 to < 75 years old) prescribed one or more hypnotic for insomnia between April 1, 2018 and March 31, 2020 with continuous enrollment for ≥ 12 months were extracted from the JMDC Claims Database. We performed multivariable logistic regression to identify factors (patient demographics and psychiatric comorbidities) associated with ORA prescription in new or non-new users of hypnotics (patients without or with hypnotics prescription history, respectively). Results Of 58,907 new users, 11,589 (19.7%) were prescribed ORA at the index date. Male sex (odds ratio [OR] 1.17, 95% confidence interval [CI] 1.12-1.22) and presence of bipolar disorders (OR 1.36, 95% CI 1.20-1.55) were associated with greater odds of ORA prescription. Among 88,611 non-new users, 15,504 (17.5%) were prescribed ORA at the index date. Younger age and several psychiatric comorbidities, such as neurocognitive disorders (OR 1.64, 95% CI 1.15-2.35), substance use disorders (OR 1.19, 95% CI 1.05-1.35), bipolar disorders (OR 1.14, 95% CI 1.07-1.22), schizophrenia spectrum disorders (OR 1.07, 95% CI 1.01-1.14), and anxiety disorders (OR 1.05, 95% CI 1.00-1.10), were associated with greater odds of ORA prescription. Conclusion This is the first study to determine the factors associated with ORA prescriptions in Japan. Our findings could help guide appropriate insomnia treatment using ORAs.